Pyogenic vertebral osteomyelitis and iliopsoas muscle abscess caused by non-typhoidal Salmonella rapidly identified by genetic testing in an immunocompetent teenage boy without hemoglobinopathies - Jun Hirai; Nobuaki Mori; Daisuke Sakanashi; Yuichi Shibata; Nobuhiro Asai; Mao Hagihara; Hiroshige Mikamo (IDCases)
Vertebral osteomyelitis caused by non-typhoidal Salmonella spp. is exceedingly rare, particularly among immunocompetent children. This report presents an unusual case of lumbar osteomyelitis and an iliopsoas muscle abscess caused by non-typhoidal Salmonella in an immunocompetent pediatric patient with a multidrug allergy. A 13-year-old boy presented with fever and lumbar pain. Diagnostic imaging revealed lumbar osteomyelitis and an iliopsoas abscess. Blood culture and initial iliopsoas puncture tissue sample test results were negative. Therefore, cefazolin was administered as empirical therapy for covering typical organisms such as Staphylococcus aureus and Streptococcus species causing vertebral osteomyelitis in healthy children. However, genetic testing of the biopsy sample of the vertebral tissue subsequently identified Salmonella spp. as the causative agent. Culture of the vertebral tissue also yielded Salmonella spp., with the O-antigen identified as type 4. Antibiotic selection was challenging because of the patient's drug allergies and age. Treatment was commenced with ceftriaxone and later changed to ampicillin owing to adverse drug reactions. The side effects, such as rash, fever, and nausea, persisted after switching to oral sulfamethoxazole-trimethoprim, which was later changed to amoxicillin. Although the treatment duration of vertebral Salmonella osteomyelitis in children is not standardized, we treated the patient for 9 weeks based on previously reported evidence. Rapid identification of the causative organism is important because vertebral osteomyelitis requires long-term treatment and treatment options may be limited, particularly in pediatric patients. Physicians should consider genetic testing to identify the causative organism of osteomyelitis.